Analysis of Internal Structure of Cement-Stabilized Macadam Based on Industrial CT Scanning - Chunyu Liang; Yinghan Wang; Guojin Tan; Lidong Zhang; Yutong Zhang; Zhihua Yu (Advances in Materials Science and Engineering)
The composition and structure of cement-stabilized macadam (CSM) is an important factor affecting its performance. Aiming at the typical suspension dense structure and skeleton dense structure, the static pressure and vibration methods were used to prepare the CSM samples. The three-dimensional internal structure characteristics of CSM were analyzed and studied by industrial CT scanning technology. By using digital image and 3D reconstruction technology, the structural parameters such as the number of 3D voids, the gradation of voids, the distribution of voids along the height direction, and the coefficient of variation of the proportion of coarse aggregate area were obtained. The results show that more than 80% of the voids in CSM are less than 1 mm3, and the number of large voids of skeleton dense gradation is more than that of suspension dense gradation under the two compaction methods. The distribution of internal voids along the height of CSM specimens cannot be changed by the compaction mode, but the vibration method can reduce its void ratio. Under different compaction methods, the variation coefficient of the coarse aggregate area ratio of two kinds of CSM mixture generally has the same change trend, and the vibration method can make its inner structure more uniform.